HUBUNGAN KEK DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH - Rapar, Christien Jane; Veronika Widiatrilupi, Raden Maria (NHM PRESS, 2024)
Background: Chronic Energy Deficiency (CED) in pregnant women is one of the main risk factors that can affect infant birth weight. CED is associated with inadequate nutritional intake, which has the potential to cause low birth weight (LBW). This study aims to analyze the relationship between CED in pregnant women and the incidence of LBW in a health facility. Objective: This study aims to determine whether there is a significant relationship between CED in pregnant women and the incidence of LBW and to identify the impact of CED on infant birth weight. Method: This study used an observational study design with a cross-sectional approach. The sample consisted of 16 pregnant women who experienced CED and gave birth at a local health facility. Data were collected through interviews and medical examinations to identify CED status and infant birth weight. Statistical analysis was performed using the chi-square test to determine the relationship between CED and the incidence of LBW. Results: The results of the analysis showed a p-value of 0.000, which means that the null hypothesis (Ho) stating that there is no relationship between CED and the incidence of LBW is rejected. On the other hand, the alternative hypothesis (Ha) stating that there is a relationship is accepted, indicating a significant relationship between CED and the incidence of LBW in pregnant women at the health facility. Conclusion: This study shows that CED in pregnant women is significantly associated with the incidence of LBW. Pregnant women who experience CED have a higher risk of giving birth to babies with low birth weight. Therefore, it is important to increase attention to meeting nutritional needs during pregnancy to prevent LBW.